(3JaSjQ GdbQBf GdYXjes - (3YHO GdQMef Hf eMeO Hf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO , GHf CHj MGJe GdQGRj ,J (B327 (3g` s
(3ChdgG (B:s
(3bhdg QHfG GNQLfG aEf YOfG aZfG XGdejf s
(3GdeNWhW jHOh YdjgG GdbOes
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdGh (B- s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs